Comprehensive market microstructure model: considering the inventory holding costs - Ryu, Doojin (Journal of Business Economics and Management, 2017)
The purpose of this study is to propose a structural market microstructure model and examine the intraday price and spread dynamics in a highly liquid market. We extend the model of Madhavan, Richardson, and Roomans to devise a comprehensive order indicator model that considers the order duration, order size, market liquidity, and most importantly, inventory holding costs. Our empirical analyses on the KOSPI200 futures market indicate that the inventory holding costs of liquidity suppliers explain a significant portion of model-implied spreads. Meanwhile, the duration and size of traded orders convey significant information content on the inventory holding component. Market liquidity is also an important consideration for futures traders who have to manage their inventory holding costs.